(untitled) (Journal of the College of Basic Education, 2025)
The convergence (performance) of history and (you do) narratively by taking it out of the perceptions of a tribal (post-modernist) audience, or even dimensionality, history is the violence of nations in its entirety, and also you see it as the opposite of (their creations) can’t be a girl with no access to it, or it’s a piece of time Rather, it and the word about performance are assumed by a combination of this and this, an unbroken torrent, a timeline that runs with a complete and unstoppable sequence, and with his undisguised sin, it is the product of a great international interaction, shrouded in the presence of human forces that have contributed to the creation of great pillars of knowledge. "Eichelman presents his perception of history as a successive chain of historical hatred, but poses this cascading perception of punishment in a non-controversial metaphysical context.This deplores (performative) history, and is assumed by one of the most important fiction writer’s tools, and by doing so it draws the frontiers of the use of history, as a crossing and integral, and wears a decent humanitarian solution, and hence we know that (performative) and history are not as contradictory as it happens in modernity Narrative of expression and export together.In this research, we will discuss the great narratives from two different perspectives, a vision (postmodernism) that is very different from what you see (performative) as an emerging theory that treats the great narratives purely as a reference moral treatment. Our choice of the Palestinian cause was a narrative of what we found fit to be a narrative of an entire people that history will always look at as a glory.